Features of current-voltage characteristics inherent to GaP light-emitting diodes with quantum wells - Konoreva, O.; Opilat, V.; Pinkovska, M.; Tartachnyk, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
In this work, GaP p-n junctions used in light-diode manufacturing were studied using the electrophysical methods at various temperatures. Current-voltage characteristics of some diodes, controlled by PC and measured in the voltage and current generator modes with various steps, have shown irregularities in the regions of negative differential resistance and specific before-breakdown part. Long-lasting relaxation of conductivity of GaP crystal with nonuniformity of defect distribution was observed. From analysis of current-flow mechanisms, it was proposed that atypical GaP light-diode electrical characteristics degradation is caused by complex traps shaped as quantum wells in the p-n junction.